EDUKASI PENCEGAHAN STRES KERJA KARYAWAN MARKETING DENGAN MEDIA POSTER DI PT. JAKABARING SPORT CITY PALEMBANG - Ezra Kristina Silitonga (LPPM Universitas Bina Bangsa, 2023)
This Internship/Work Practice activity is carried out to provide understanding to employees of PT. Jakabaring Sport City Palembang, especially in the Marketing Division regarding WORK STRESS and its prevention efforts. This is done because the employees especially in the marketing division do not know what WORK STRESS is, WORK STRESS factors, and efforts to prevent WORK STRESS. The method used in this education is POSTER. The results of the activity show that the employees, especially the marketing division, understand the dangers of WORK STRESS, know about the factors of WORK STRESS and the application of WORK STRESS prevention